Spray freeze drying for protein encapsulation: Impact of the formulation to morphology and stability. Issue 1 (3rd January 2023) - Baldelli, Alberto; Cidem, Aylin; Guo, Yigong; Ong, Hui Xin; Singh, Anika; Traini, Daniela; Pratap-Singh, Anubhav
Abstract: Proteins, the building blocks of life, are increasingly being used as therapeutics for treating several diseases. Yet, there are challenges in the delivery of highly labile materials like proteins, which is often circumvented with the help of encapsulation for targeted delivery and enhanced stability. Spray drying technology has recently been employed for encapsulation due to its' low cost and scale-up capabilities, yet the high temperatures of drying air makes the technology unsuitable for proteins. More recently, spray freeze drying has evolved as an emerging technology that combines spray drying with freeze drying by using low temperatures, and is thus suitable for maintaining the stability of proteins. This study investigates the correlation between formulation parameters and the properties of protein encapsulated microparticles prepared by spray freeze drying. Morphology was investigated using microscopic methods, and protein stability was examined using infrared and mass spectrometry. By using bovine serum albumin, we verify that increasing the total weight to 15 mg/ml results in microencapsulates with a projected area equivalent diameter of 100 µm larger. We demonstrate that some types of amino acids are essential for shell formation; however, glutamine generates an increase in dimer areas in mass spectra of 5.5. D-Mannitol is the suggested carrier for high encapsulation efficiency (above 90 %). The formulation containing polyvinylpyrrolidone, mannitol, and leucine (at 6, 9, and 2 mg/ml, respectively) produced the lowest reduction in the stability of a few types of proteins; deconvoluted infrared peaks show a difference of less than 2% compared to the free protein. Understanding the spray freeze drying phenomenon for protein encapsulation would allow the control over morphological and chemical properties of microparticles containing active proteins. Graphical Abstract: UF0001